Pontormo : drawings - Pontormo, Jacopo da, 1494-1556; Nigro, Salvatore S (New York : H.N. Abrams, 1992)
The agitated and contorted figures of 16th-century Florentine Mannerist painter Jacopo da Pontormo still beckon us to fathom their psychological depths, as revealed by this collection of 77 full-page color reproductions of his drawings. Pontormo's androgynous male youths wrestle with inner demons. His highly elongated, smiling Three Graces are not of this world. A penitent St. Jerome, in his painful self-inquisition, is emblematic of the artist's turmoil. Even his chubby infants twist and grimace, confirming Italian scholar Nigro's observation that Pontormo and his circle dwelled on ``the body in all its aspects of pathological misery.'' Featured in this elegant volume are calm, sensitive portraits that contrast with the more nervous works, plus ethereally majestic studies for frescoes in the chapel of San Lorenzo which depict strangely haughty angels, Adam and Eve, Noah in the Flood and a multitude of dead bodies
Includes bibliographical references (page 21)
Translated from Italian and German
Keywords: Pontormo, Jacopo da, -- 1494-1556 -- Catalogs -- Themes, motives